Non-phosgene route for the synthesis of methyl phenyl carbamate using ordered AISBA-15 catalyst - Lucas, Nishita; Amrute, Amol P.; Palraj, K.; Shanbhag, G. V.; Vinu, Ajayan; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2008)
Methyl phenyl carbamate (MPC) has been synthesized Under liquid phase conditions from dimethyl carbonate and aniline by using mesoporous AISBA-15 catalyst. The catalyst with different Si/Al ratio was synthesized by isomorphous Substitution of aluminium into the framework of siliceous SBA-15. The structural integrity of the catalyst system was diagnosed with the help of various characterization techniques Such as X-ray diffraction, Surface analysis, and the acidity measurement has been done by TPD using ammonia as probe molecule. AISBA-15 (Si/Al = 10) exhibited highest catalytic activity in the synthesis of MPC under the reaction Conditions Studied. The effect of parameters Such as molar ratio of reactants, catalyst concentration. reaction temperature and time on the conversion of aniline was investigated. The results demonstrated that an aniline conversion of 99% and MPC selectivity of 71% were achieved when the reaction was carried out at 100 C, DMC to aniline mole ratio of 10 with 5% of catalyst (wt% of total reaction mixture) for 3 h. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: amines; Dimethyl carbonate; Mesoporous AISBA-15; Methoxycarbonylation; Methyl phenyl carbamate

[Ru(salen)(NO)] complex encapsulated in mesoporous SBA-16 as catalyst for hydrogenation of ketones - Bordoloi, Ankur; Amrute, Amol P.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
SBA-16 mesoporous silica with cubic lm3m structure was synthesized using Pluronic F127 poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer (EO106PO70EO106) and it blends with Pluronic P123 triblock copolymer (EO20PO70EO20) as supramolecular templates. The resulting material was used for encapsulating [Ru(salen)(NO)] complex and used in the hydrogenation of ketones to the corresponding alcohols. The pore entrance size of SBA-16 was precisely tailored by silylation with diphenyldichlorosilane to trap [Ru(salen)(NO)] complex in the cage of SBA-16. Small angle XRD, N-2 sorption measurements, UV-Vis and FT-IR analysis evidences the structural integrity of mesoporous silica as well as the complex. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Encapsulation; Hydrogenation; Ketones; SBA-16; [Ru(salen)(NO)] complex

Sol-gel synthesis of MoO(3)/SiO(2) composite for catalytic application in condensation of anisole with paraformaldehyde - Amrute, Amol P.; Bordoloi, Ankur; Lucas, Nishita; Palraj, K.; Halligudi, Shivaraj B. (Catalysis Letters, 2008)
MoO(3)/SiO(2) composite with varying amounts of MoO(3) loading (1-20 wt.%) were prepared by sol-gel method and calcined at 500 C. These catalysts were employed for the liquid phase condensation of anisole with paraformaldehyde. All the catalysts were characterized by N(2) sorption, XRD, and NH(3)-TPD. The activities of synthesized MoO(3)/SiO(2) catalysts were compared with p-toluene sulfonic acid (p-TSA), the most frequently used catalyst for the condensation reactions, and with a supported metal oxide (WO (x) /ZrO(2)). Under the similar reaction conditions, synthesized 10 wt.% MoO(3)/SiO(2) catalyst calcined at 500 C was found to be the most active in the condensation of anisole with paraformaldehyde.
Keywords: 4; 4'-Dimethoxydiphenylmethane; Condensation of anisole; MoO(3)/SiO(2) composites; Paraformaldehyde; Sol-gel synthesis

Titania supported silicotungstic acid: an efficient solid acid catalyst for veratrole acylation - Waghmare, Nilesh G.; Kasinathan, Palraj; Amrute, Amol P.; Lucas, Nishita; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
Titania supported silicotungstic acid (STA) with different STA loading (10-25 wt%) and calcination temperature (650-750 degrees C) were prepared by wet impregnation method. The catalysts have been represented by a general formula xSTiO(2)y (where x denotes wt%, S denotes STA and y denotes calcination temperature in degrees C). These catalysts were characterized by techniques such as X-ray diffraction, surface analysis, FTIR-pyridine and TPD-NH(3) and were used as heterogeneous solid acid catalysts in the liquid phase acylation of veratrole with acetic anhydride (Ac(2)O). It was found that 20STiO(2)700 gave the highest activity in acylation reaction due to its highest acidity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: acetic anhydride; Acylation; Silicotungstic acid; titania; veratrole

Comparative study on liquid phase alkylation of 2-methylnaphthalene with long chain olefins using different solid acid catalysts - Lucas, Nishita; Bordoloi, Ankur; Amrute, Amol P.; Kasinathan, Palraj; Vinu, Ajayan; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
A comparative study has been made over a variety of solid acid catalysts, which include isopoly and heteropoly ions supported on various supports such as zirconia, titania, a large variety of zeolites and a couple of mesoporous materials for liquid phasealkylation of 2-methylnaphthalene with 1-octene.All the catalyst systems were characterized by nitrogen sorption analysis, X-ray diffraction and NH(3)-TPD. Inspite of their high acid amounts zeolites gave poor catalytic performance due to their diffusional constraints; on the other hand mesoporous materials lacked diffusional constraints but due to their low acid amounts resulted in poor conversions. lsopoly and heteropoly ions supported on zirconia and titania were found to be catalytically active for the reaction due to total surface acidity. Among them, isopolytungstate supported on zirconia exhibited the best catalytic activity and was used for further optimization of reaction conditions. Excellent conversions of all olefins (>92%) with high selectivity of monoalkylmethylnaphthalene (>95%) was obtained under optimized reaction conditions. The catalyst could be recycled for several times without any obvious loss of its activity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 2-Methylnaphthalene; Alkylation; Long chain olefins; Zirconia

MoO3/SiO2: an efficient and selective catalyst for the synthesis 1,3-dioxolane and 1,3-dioxane - Amrute, Amol P.; Sahoo, Suman; Bordoloi, Ankur; Hwang, Young Kyu; Hwang, Jin-Soo; Halligudi, Shiva B. (Catalysis Communications, 2009)
A series of MoO3/SiO2 catalysts with varying amounts of MoO3 has been synthesized and the catalytic activities of these were compared with the known solid acid catalysts in the synthesis of 1,3-dioxolane. MoO3/SiO2 catalyst showed a better activity and selectivity in 1,3-dioxolane synthesis compared to the other catalysts. MoO3/SiO2 catalyst system was further successfully applied for the synthesis of 1,3-dioxanes in the Prins cyclization of olefins and formaldehyde. The proposed catalyst was thermally stable and could be recovered and reused at least in four consecutive cycles with no significant loss in the substrates conversions and products selectivities. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 1; 3-Dioxolanes; Cycloaddition; MoO3/SiO2; Prins cyclization; Sol-gel method; solid acid catalysts